The Influence Of Kintan Media On Knowledge And Self-Efficacy Of Hypertension Prevention In Pkk Groups In Simpang Tiga Village, Samarinda - Faeris Suaib; Desie Rahmawati; Dian Ardyanti; Sri Hazanah (Journal of Creative Power and Ambition (JCPA), 2026)
Hypertension is still a public health issue in Samarinda City, with cases rising from 33,555 in 2020 to 69,156 in 2024. This situation highlights the importance of health education using KINTAN (Health Information Fan) as a way to boost people's knowledge and self-confidence in preventing hypertension. This study aimed to analyze the impact of health education using KINTAN media on knowledge and self-efficacy regarding hypertension prevention in PKK groups in the Simpang Tiga Subdistrict of Samarinda. This study used a quantitative method with a pre-experimental approach and a one-group pre-test post-test design. The sample size was determined using the Lemeshow formula, resulting in 39 respondents. Data were collected using knowledge and self-efficacy questionnaires and then analyzed univariately and bivariately using the Wilcoxon test. Before the intervention, most respondents had good knowledge, with 31 respondents (79.5%), adequate knowledge with 4 respondents (10.3%), and poor knowledge with 4 respondents (10.3%). After the intervention, the number of respondents with good knowledge increased to 34 (87.2%), those with adequate knowledge remained at 4 respondents (10.3%), while poor knowledge decreased to 1 respondent (2.6%). For the self-efficacy variable, the high category increased from 28 respondents (71.8%) to 35 respondents (89.7%), while the low category decreased from 11 respondents (28.2%) to 4 respondents (10.3%). The Wilcoxon test results showed that health education using KINTAN media had an effect on knowledge (ρ = 0.007) and self-efficacy (ρ = 0.010). Therefore, health education using KINTAN media has an effect on increasing knowledge and self-efficacy regarding hypertension prevention among the PKK Group in the Simpang Tiga Subdistrict of Samarinda.